KONFIGURASI SISTEM KEAMANAN JARINGAN - Gani, Alcianno G (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2019)
Along with the development of technology in the world of computing, human needs are also increasingly complex in its use for the development of these technologies. This is something that is only natural and supports each other between both technology and human needs. Technology will continue to be created from time to time, from the simple to the very sophisticated technology. With technology, it is expected that all human activities can be solved more easily, quickly and accurately. One of them is the existence of a network system. Through the network there are many conveniences that can be felt including sharing hardware, sharing software, facilitating communication between network users and sharing data and information more easily. Long distances are no longer a barrier to being able to get data and information quickly and safely. In network systems also need to be considered the security problem in order to avoid things that are not desirable, such as being attacked by a virus or reading data by unwanted parties.